Exercise-induced diaphragm fatigue in a Paralympic champion rower with spinal cord injury - Tiller, N. B.; Aggar, T. R.; West, C. R.; Romer, L. M. (Journal of Applied Physiology, 2018)
The aim of this case report was to determine whether maximal upper body exercise was sufficient to induce diaphragm fatigue in a Paralympic champion adaptive rower with low-lesion spinal cord injury (SCI). An elite arms-only oarsman (age: 28 yr; stature: 1.89 m; and mass: 90.4 kg) with motor-complete SCI (T12) performed a 1,000-m time trial on an adapted rowing ergometer. Exercise measurements comprised pulmonary ventilation and gas exchange, diaphragm EMG-derived indexes of neural respiratory drive, and intrathoracic pressure-derived indexes of respiratory mechanics. Diaphragm fatigue was assessed by measuring pre- to postexercise changes in the twitch transdiaphragmatic pressure (Pdi,tw) response to anterolateral magnetic stimulation of the phrenic nerves. The time trial (248 ± 25 W, 3.9 min) elicited a peak O2 uptake of 3.46 l/min and a peak pulmonary ventilation of 150 l/min (57% MVV). Breath-to-stroke ratio was 1:1 during the initial 400 m and 2:1 thereafter. The ratio of inspiratory transdiaphragmatic pressure to diaphragm EMG (neuromuscular efficiency) fell from rest to 600 m (16.0 vs. 3.0). Potentiated Pdi,tw was substantially reduced (-33%) at 15-20 min postexercise, with only partial recovery (-12%) at 30-35 min. This is the first report of exercise-induced diaphragm fatigue in SCI. The decrease in diaphragm neuromuscular efficiency during exercise suggests that the fatigue was partly due to factors independent of ventilation (e.g., posture and locomotion). NEW & NOTEWORTHY This case report provides the first objective evidence of exercise-induced diaphragm fatigue in spinal cord injury (SCI) and, for that matter, in any population undertaking upper body exercise. Our data support the notion that high levels of exercise hyperpnea and factors other than ventilation (e.g., posture and locomotion) are responsible for the fatigue noted after upper body exercise. The findings extend our understanding of the limits of physiological function in SCI.